2005
DOI: 10.1007/s11085-005-5704-3
|View full text |Cite
|
Sign up to set email alerts
|

KCl Induced Corrosion of a 304-type Austenitic Stainless Steel at 600°C; The Role of Potassium

Abstract: The influence of KCl on the oxidation of the 304-type (Fe18Cr10Ni) austenitic stainless steel at 600 • C in 5% O 2 and in 5% O 2 + 40%H 2 O is investigated in the laboratory. The samples are coated with 0.1 mg/cm 2 KCl prior to exposure. Exposure time is 1-168 h. Uncoated samples are exposed for reference. The oxidized samples are analyzed by ESEM/EDX, XRD and AES. The results show that small additions of potassium chloride strongly accelerate high temperature corrosion, the oxide thickness being up to two ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
165
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(174 citation statements)
references
References 19 publications
9
165
0
Order By: Relevance
“…Initiation and sustaining mechanisms for the corrosion process are still being discussed in literature [22,27,30,38,39]. For Cr-containing alloys under oxidizing conditions, the K-induced breakaway corrosion of the initial protective Cr2O3 layer has been reported as the initiation process (equation 1) [5,21,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initiation and sustaining mechanisms for the corrosion process are still being discussed in literature [22,27,30,38,39]. For Cr-containing alloys under oxidizing conditions, the K-induced breakaway corrosion of the initial protective Cr2O3 layer has been reported as the initiation process (equation 1) [5,21,40].…”
Section: Discussionmentioning
confidence: 99%
“…Simplified laboratory-scale corrosion studies using synthetic deposits (KCl, NaCl, CaCl2, etc. ), and in some cases, under HCl-or H2O-containing gaseous atmospheres, have revealed the respective roles of K and Cl in initiating and catalyzing the corrosion of alloys under oxidizing conditions [4,5,[21][22][23][24][25][26][27][28][29][30]. The results from characterization of corrosion products from most of these laboratory studies point towards an active oxidation type of mechanism.…”
Section: High Temperature Corrosion Under Laboratory Conditions Simulmentioning
confidence: 96%
“…The evidence from SEM/EDX, XRD and IC clearly shows that KCl reacts to form K 2 CrO 4 on the alloy surface. As noted in the introduction, FeCrNi and FeCrAl alloys have been reported to react with KCl and water vapour to form K 2 CrO 4 [7,8,13,14] according to Reaction (1). For standard state conditions it is found that DG 873K = 90.5 kJmol -1 K [22] for Reaction (1).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the high-temperature corrosion of chromia-forming steels in an oxidising environment is accelerated by alkali chlorides and by high concentrations of water vapour [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The accelerated effect of water vapour has been shown to be connected to chromia evaporation in the form of CrO 2 (OH) 2 [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…KCl induced corrosion of high temperature materials has been the subject of a number of investigations [6][7][8][9][10][11][12][13] to clarify the mechanism of attack in order to pave the way for the development of advanced high temperature resistant materials. Laboratory investigations have shown that the alkali earth metal plays a role in the initial corrosion process [8,10,[14][15][16][17].…”
mentioning
confidence: 99%